Study on the pavement design for commercial territory of Kuala Lumpur, Malaysia - Zakaria, Nadiah; Abu Eusuf, Muhammad; Hj. Baharuddin, Zainul Mukrim; Othman, Rashidi (2008)
This paper presents the results of a field experiment conducted within DUM to test the surface temperature due to air temperature as long as to point out the potential and constrains of pavement design within commercial area in KL Central. It evaluates the characters and properties of pavement, the potential of designated pavement for traffic calming and also identifying the problems of pavement. In the context of su3l:ainabLe watershed management, porous pavement is the most suitable material that can be used within urban area. Rain that fell on porous surfaces would percoillte through to pipes laid underneath for harvesting and treatment; this is an attractive alternative for conventional pavement.